Talqin Zikir sebagai Metode Dakwah - Luthfi, Danial (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
This paper reveals the concept and process of talqin dhikr, the success of talqin dhikr as a method of da'wah and the implications of talqin zikir for the development of contemporary da'wah method. This research used qualitative approach and case study research method with observation and interview techniques. The results showed that talqin dhikr is a method of dakwah that answer the problems of modern society. Talqin dhikr both in congregate and individually could bring the members to the good condition ini emotional-spiritual aspect (al-'âthifiy); rational aspects (al-'aqliy); and sensory aspect (al-hissiy). Talqin dhikr offer to fulfil the needs of modern society for the emptiness of spirituality through a short and fast process and also managed to change the emotional-spiritual state, perspective and member’s mindset and allow them to move positive activites. Talqin dhikr become a significant contribution to the development of da'wah.